8 Rapid analgesia for prehospital hip disruption (rapid). (16th April 2018) - Bulger, Jenna; Brown, Alan; Evans, Bridie A; Fegan, Greg; Ford, Simon; Guy, Katy; Jones, Sian; Keen, Leigh; Khanom, Ashrafunnesa; Pallister, Ian; Rees, Nigel; Russell, Ian T; et al.
Abstract : Aim: Pain relief in prehospital care is a challenge in trauma, especially for those with hip fractures, whose injuries are difficult to immobilise and whose long term outcomes may be adversely affected by administration of opiates. Fascia Iliaca Compartment Block (FICB) is routinely undertaken by hospital clinicians, but has not been fully evaluated for use by paramedics in prehospital care. Method: Nineteen paramedics were trained; they randomly allocated eligible patients to trial arms using audited scratchcards. Patients were followed up to assess availability of outcomes including quality of life, length of admission, pain scores, and adverse events. Findings were analysed against pre-specified progression criteria. Results: Seventy-one patients were randomised by paramedics (28/6/16 – 31/7/17); 57 consented to follow up. The only outcome which reached a statistically significant difference between groups was the proportion of participants who received morphine (38% difference between groups 95% CI: −61.88 to −15.79). There was a difference of approximately nine days in the length of admission between trial arms (mean difference 9.12 (95% CI: −20.51 to 2.27). Conclusion: RAPID met its pre-specified progression criteria; a funding application for a fully-powered RCT will therefore be submitted. We will consider the use of length of stay as the primary outcome, as findings indicated a difference between groups without reaching statistical significance. Conflict of interest: None Funding: Health and Care Research Wales, Research for Patient and Public Benefit.